Úlcera por pressão em idosos institucionalizados: associação da incidência com os fatores de risco, avaliação funcional e nutricional - Silva, Mirian Alves da (2014)
Populational aging is a reality placed to most societies today. In recent decades, the significant increase of the elderly population has changed the brazilian demographic profile. The family rearrangements, that to a greater or lesser degree weaken family bonds so necessary for that human caring; the active participation of women in labor market, who has historically figured as responsible for the care; the shortage of alternatives for families to keep their old at home and those elderly without family reference are some of the factors that have driven the demand for Homes for the Aged. Among the main clinical institutionalization causes, there are the sequels of chronic noncommunicable diseases, associated with weaknesses caused by the skin aging process and by the peculiarities of each elderly that predisposes the elderly to the development of skin lesions, including pressure ulcers. Given the multifactorial genesis of the pressure ulcers, this study aims to examine the association of risk factors such as functional and nutritional assessment and its influence on the incidence of pressure ulcers in the elderly residents in Homes for the Aged in João Pessoa. This is a population-based study, prospective (incidence), descriptive and exploratory with quantitative approach. Had as an investigative unit all elderly residents (324) of the all Homes for the Aged in João Pessoa-PB. Structured into two phases: in first phase, all medical registers and elderly were examined and the data were recorded on a proper instrument, the other data were obtained from the answers to a questionnaire, applying Braden, Katz and Mini Nutritional Assessment scales and from the examination of 324 elderly`s skin; in the second phase, which included the elderly who had Braden score ≤ 18 (constant 142 elderly), four examinations were conducted in consecutive weeks, which included the physical examination of the skin. The results showed an incidence of 51% of elderly with pressure ulcer. According to Braden scale, in the higher risk categories that include elderly with pressure ulcers, there are the following subscales: moisture (skin very moist), nutrition (probably inadequate) and friction and shear (potential problem), all of them with differences statistically significant. As to nutritional status, 64.4% of elderly who developed pressure ulcers were classified as malnourished. It was also found that 79.46% had only one ulcer. The most common locations of the pressure ulcers were the sacral region with 32.87%, followed by the gluteal regions with 20.55% and the lateral margins of the feet with 9.59%. It was observed that 49.32% had stage II pressure ulcers. The low participation of nurses in care, the examination of elderly and the realization of educational meetings with the multidisciplinary team and caregivers were especially noticeable. The inadequacy of human resources and the lack of active participation of the State influence the absence of preventive programs and the promotion of an active aging.